Management information system data processing results of sports talent identification test: Borneo sport talent Id software implementation - Buhari, M. R.; Hidayanto, D. N.; Sjamsir, H.; Haryaka, U.; Syamsudduha, S. (Educational Studies: Conference Series, 2023)
This research resulted in a data processing system application program for sports talent identification test results aged 11-15 years which can accelerate the provision of information about the classification of potential gifted children and recommendations for sports branches based on anthropometric data parameters and biometric data. The sample in the study was 50 students in Samarinda Kota and Samarinda Ulu sub-districts using the cluster area sampling technique. The data collection technique uses a talent identification test battery instrument. In completing this research, the author uses a database-based programming language in the Borneo Sport Talent software. The results showed: (1) Borneo Sports Talent Id can be used as a system for processing data on talent identification results effectively and efficiently, (2) Talent classifications were found, namely: 10% of children have potential, 22% of children have sufficient potential, 32% of children have less potential, and 36% of children have no potential, (3) Recommendations for potential sports: volleyball, rowing, soccer, fencing, swimming, gymnastics, and rock climbing, and athletics in running, jumping, and throwing events.